DELINEATING RESISTIVITY VALUES OF POTENTIAL GEOTHERMAL AREAS ALONG THE BOGOR FAULT USING 2D MAGNETOTELLURIC INVERSION - Hardiansa, Debi; Farid, M; Hadi, Arif Ismul; Al-Ansory, Andre Rahmat; Raihana, Hana; Rahmawati, Nurul 'Ilmi (Indonesian Physical Review, 2025)
Kepahiang Regency, located in an active fault zone, has great geothermal potential with an estimated capacity of up to 154 MW(e), making it a strategic renewable energy source to be developed. This research discusses the geothermal potential in the Kabawetan area, Kepahiang, Bengkulu. The main objective of this research is to evaluate the potential of geothermal resources around the Bogor segment by analyzing the subsurface structure using the Magnetotelluric inversion method and 2D resistivity modeling, in order to identify prospective geothermal reservoir zones. It can evaluate the potential of geothermal reservoirs in Kepahiang. The method used is the Magnetotelluric method, which utilizes the Earth's natural electromagnetic field to determine the distribution of resistivity in the subsurface. The results of 2D modeling with the MT method show potential zones associated with variations in subsurface thermal conditions and the presence of conductive clay minerals with resistivity values between 0.14-1 Î©m. These minerals are thought to be associated with the overburden (reservoir) of the geothermal system that has a depth of 2-4 km. The subsurface layer containing hot water and steam originating from heat emitted from the earth's core with a resistivity value of 2.5-45 Î©m at a depth of 1-4 km is thought to be caprock in the geothermal system, a resistivity value of 120-800 Î©m is thought to be hot rock with a depth between 1.5-10 km. It is estimated that there is a type of andesite rock that has been fractured as a reservoir of geothermal fluid. The findings of this research are expected to contribute to renewable energy as an alternative energy in the future, not only for energy needs but also for regional economic development through tourism and to support sustainable governance.